Meningkatkan Hasil Belajar Ipa Menggunakan Model PBL, SAVI Dan Talking Stick Pada Siswa Kelas IV - Nurlaila Rahmadaniyati; Tika Puspita Widya Rini (CV. ITTC INDONESIA, 2023)
Education is something that is taken seriously because it has a major impact on individual development. This is in line with the implementation of the 2013 curriculum learning system which demands to develop the potential and skills of students, as well as provide a deeper and contextual understanding in various subjects. One of the 2013 curriculum learning is science, this learning is expected to meet the ideal conditions set out in BSNP 2006. In reality, in Class IV SDN Tanggul Rejo 1 has not met the ideal conditions. This can be seen in students less able to develop knowledge and understanding of science concepts, students are less enthusiastic about developing curiosity due to lack of innovation in learning such as lack of utilization of learning media, students who are less actively involved in learning because learning is still less two-way so that students are still lacking in skills to solve a problem, and student learning outcomes are still low or below the Minimum Completeness Criteria. Through the Problem Based Learning model combined with SAVI and Talking Stick is expected to be one of the solutions to solve these problems. This research uses a qualitative approach with the type of Classroom Action Research. Data collection on teacher and student activities was obtained through observation sheets and student learning outcomes were obtained through individual tests. Data analysis in this study used descriptive analysis and cross tabulation techniques described by tables, graphs and interpretation with percentages. The results showed that the activities of teachers, students and learning outcomes at meetings I to IV increased to reach 100%. Based on this research, it can be concluded that the Problem Based Learning, SAVI, and Talking Stick models can improve student activity and learning outcomes.